Average velocity of bedload particle in uniform open channel flows - Tang, Qi. (2013)
Use of laboratory flume model to define the reach-averaged velocity of a single spherical particle rolling over an ideally closely packed particle bed obtained under different uniform flow conditions. This experiment aims at simulating the bedload particle rolling and saltation in rough open channels as a function of the following variables: (1) water surface or friction slope Sf, (2) flow depth h, (3) particle size ds, (4) viscosity of the fluid ν, (5) excess specific gravity Δ, and (6) gravitational acceleration g. The designed flume flow specifications has been well controlled and measured, flow was relatively shallow (1.2 < h/ds < 2.0), the Froude number within a wide range (0.7 < Fr < 1.6), friction slope varied (0.005 < Sf < 0.032). This study model may be applicable to a real condition such as rapids over gravel beds at mountain vale.